2016
DOI: 10.4314/tjpr.v15i10.9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leishmanial and cytotoxic activities of extracts from three Pakistani plants

Abstract: Purpose: To evaluate the in vitro and in vivo anti-leishmanial and cytotoxic activities of extracts of different parts of Lawsonia Inermis, Morus nigra and Ziziphus mauritiana. Methods: The methanol extracts of all three plant materials at concentrations of 10 -100 µg/mL were tested for their in vitro anti-leishmanial effects on L. tropica KWH23 promastigotes for 24 -48 h, relative to negative control and amphotericin-B (standard drug). For in vivo anti-leishmanial activity, the extracts were tested against L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…The in vitro antileishmanial growth inhibition assay was adopted from Iqbal et al (2016b). Promastigotes of L. tropica were cultured in RPMI-1640 medium containing 10% FBS, 200 U/mL of penicillin, and 0.2 mg/mL of streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro antileishmanial growth inhibition assay was adopted from Iqbal et al (2016b). Promastigotes of L. tropica were cultured in RPMI-1640 medium containing 10% FBS, 200 U/mL of penicillin, and 0.2 mg/mL of streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…In Pakistan, it is widely found in the Dera Ismail khan and Bannu districts of the Khyber Pakhtunkhwa province. L. inermis is extensively used for different medicinal purposes, and possess a variety of biological and pharmacological activities, including antioxidant ( Dasgupta et al, 2003 ), antibacterial ( Ali et al, 2001 ), antifungal ( Singh and Pandey, 1989 ), antiviral ( Khan et al, 1991 ), antiparasitic ( Okpeton et al, 2004 ), analgesic ( Mohsin et al, 1989 ), cytotoxic ( Ali and Grever, 1998 ), antidiabetic ( Arayne et al, 2007 ), antileishmanial ( Iqbal et al, 2016a , b ) and protein glycation inhibitory activity ( Sultana et al, 2009 ). L. inermis is chemically well investigated ( Semwal et al, 2014 ), and more than 135 compounds have been reported from the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1-5 were selected due to their promising in vitro anti-leishmanial effects [22] against L. tropica. All tested compounds showed a cure rate between 97.02 and 75.02 % at 3 mg/kg concentration (for 5 days) whereas cytotoxic effects against lymphocytes in terms of IC 50 values ranging between 4.15 and 10.27 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Dial micrometer was used to note the difference between size of the lesion in infected and uninfected mice weekly. Before and after treatment, needle aspirations were taken from the lesions [22]. To detect amastigotes under upright microscope, Giemsa stain was used, and the samples were examined under oil immersions.…”
Section: In Vivo Testmentioning
confidence: 99%
See 1 more Smart Citation